Oncocytic Schneiderian papilloma of frontal sinus - Kalfert, David; Laco, Jan; Celakovský, Petr; Smatanová, Katarína; Ludvíková, Marie (Acta medica (Hradec Kralove), 2013)
Oncocytic Schneiderian papilloma (OSP) is one of the three morphologically distinct tumors that arise from Schneiderian membrane (the others include exophytic papilloma and inverted papilloma). OSP almost always occurs unilaterally in the paranasal sinuses, usually in the maxillary sinus, ethmoid cells or sphenoid sinus. We report a case of a 64-year-old woman with OSP arising from the left frontal sinus. In the report herein, we describe an OSP originating in the region of frontal sinus, which, to the best of our knowledge, represents the first documented example in English literature of OSP developing in this anatomical site.
Keywords: diferenciální diagnóza; Female; Frontal Sinus; nádory vedlejších dutin nosních; Otorhinolaryngologic Surgical Procedures; ženské pohlaví; biopsie; Tomography, X-Ray Computed; lidé; Diagnosis, Differential; otorinolaryngologické chirurgické výkony; Biopsy; sinus frontalis; Paranasal Sinus Neoplasms; počítačová rentgenová tomografie; lidé středního věku; Papilloma; Middle Aged; papilom; Humans